Study of the diffusion layers of the nbta-ti uperconducting alloy - Tuan Renosto, Sergio; Souza Ribeiro, Lívia; Bormio-Nunes, Cristina (Revista Ciências Exatas, 2009)
The optimization of flux line pinning in type II superconductors, as NbTi and Nb3Sn, is the most efficient form to improve the transport properties of these materials. The present work has as objective the manufacture of a NbTaTi multifilament wire with Artificial Pinning Centers (APC). A bar of Ti introduced in a NbTa tube has the dimensions reduced by means of mechanical deformation, swaging and drawing, to produce the monofilament. The multifilament wire is produced by assembling 169 pieces of the monofilament wire in a Cu tube, followed also by swaging and drawing. At some point of the mechanical deformation process a heat treatment is applied in order to produce the ternary alloys NbTaTi by solid state diffusion. Some pure Ti and Nb- Ta is left in order to act as APC. The controlled obtain of pinning centers by previous calculation of size and distribution is advantageous in order to get the optimized critical current densities. The microstructure of the material will be characterized relative to the diffusion layer size and composition as well as the size of nonreacted pure Ti and Nb-Ta-Ti.